A prospective, randomized, open-label study to compare the efficacy and safety of metformin versus metformin and fluoxetine in patients of type 2 diabetes mellitus with mild depression - Aggarwal, Deepali; Randhawa, Gurpreet Kaur; Chander, Rakesh (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Type 2 diabetes mellitus (T2DM) and depression often occur together, increasing morbidity and mortality. While metformin shows potential antidepressant effects, its comparative efficacy and safety versus metformin-fluoxetine (MF) combination in T2DM patients with mild depression required further study. Methods: This prospective, randomized, open-label study involved 60 patients (18-65 years) with T2DM and mild depression (HDRS 8-13) over 90 days. Group A received metformin 500 mg twice daily (n=30), while group B received metformin 500 mg twice daily plus fluoxetine 40 mg daily (n=30). Primary outcomes included glycemic parameters (FPG, HbA1c) and depression scores (HDRS, CGI). Safety, quality of life, and compliance were also assessed. Results: Baseline parameters were comparable between groups. Both groups showed highly significant improvements (p<0.001) in glycemic control and depression scores. Over 60 days, group A showed 20% HDRS improvement versus group B’s 10%; CGI-I was 3.33% in A versus 0% in B. By 90 days, HDRS improvement was 100% in group A versus 93.33% in B, while CGI-S and CGI-I improvements were 100% for both groups. No significant intergroup differences were observed for efficacy (p>0.05). Expected adverse effects were lower with metformin (28.33%) versus fluoxetine therapy (66.67%), all mild. Both groups demonstrated highly significant (p<0.001) QOL improvement and good compliance (≥85%). Conclusions: Both treatments effectively improved glycemic control and depression symptoms. Metformin monotherapy demonstrated comparable efficacy and safety to the combination therapy of metformin and fluoxetine for managing mild depression in T2DM patients.